2020
DOI: 10.3390/ijms21134645
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activation of Toll-Like and NOD Receptors by Complementary Antigens as Facilitators of Autoimmune Disease: Review, Model and Novel Predictions

Abstract: Persistent activation of toll-like receptors (TLR) and nucleotide-binding oligomerization domain-containing proteins (NOD) in the innate immune system is one necessary driver of autoimmune disease (AD), but its mechanism remains obscure. This study compares and contrasts TLR and NOD activation profiles for four AD (autoimmune myocarditis, myasthenia gravis, multiple sclerosis and rheumatoid arthritis) and their animal models. The failure of current AD theories to explain the disparate TLR/NOD profiles in AD is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 172 publications
(238 reference statements)
0
24
0
Order By: Relevance
“…The DAMPs activating NLRP3 include cholesterol crystals and amyloid proteins such as those found in Alzheimer’s disease and diabetes [ 47 ]. Thus, once an innate immune response has been activated by the presence of foreign antigens, it may be maintained by the release of host antigens if the foreign antigens stimulate ongoing cellular damage or if an autoimmune disease process is initiated [ 51 ].…”
Section: Innate Immune System Receptor Activation In Cytokine Stormentioning
confidence: 99%
See 4 more Smart Citations
“…The DAMPs activating NLRP3 include cholesterol crystals and amyloid proteins such as those found in Alzheimer’s disease and diabetes [ 47 ]. Thus, once an innate immune response has been activated by the presence of foreign antigens, it may be maintained by the release of host antigens if the foreign antigens stimulate ongoing cellular damage or if an autoimmune disease process is initiated [ 51 ].…”
Section: Innate Immune System Receptor Activation In Cytokine Stormentioning
confidence: 99%
“…While any particular PAMP or DAMP activates only one or two innate receptor pathways, every innate receptor synergizes with some limited set of other receptors, so that combinations of PAMPs and DAMPs can initiate far greater releases of cytokines than individual ones. Figure 2 A,B summarize the currently known sets of innate receptor synergisms based on two previous reviews [ 51 , 56 ] supplemented by additional sources that were found during the process of researching the present paper [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. For example, TLR4 synergizes with multiple TLR, especially TLR2 and TLR9, as well as NLRP3 [ 51 , 56 ].…”
Section: Innate Immune System Receptor Activation In Cytokine Stormentioning
confidence: 99%
See 3 more Smart Citations